Synthesis of benzo[b]phosphole‐based alkynylgold(I) complexes with resistive memory properties modulated by donor–acceptor chromophores. (21st September 2021) - Cheng, Yat‐Hin; Hong, Eugene Yau‐Hin; Leung, Ming‐Yi; Lai, Shiu‐Lun; Yam, Vivian Wing‐Wah
Abstract: A class of benzo[ b ]phosphole‐based alkynylgold(I) complexes has been synthesized and characterized. These complexes share a similar benzo[ b ]phosphole ligand, in which the phosphole moiety is substituted with various π‐conjugated units with different donor strengths, namely phenoxazinylphenyl, tris(di‐ tert ‐butylcarbazolyl)phenyl and 2, 4‐dimethylphenyl moieties. These phosphole‐containing gold(I) complexes are found to be strongly luminescent in toluene with tunable emission maxima and possess solvatochromic behaviors, suggesting an emission of metal‐perturbed intraligand charge transfer origin. Cyclic voltammetry studies reveal that the presence of gold(I) metal center strongly perturbs the electronic properties of the phosphole moiety of the resultant complexes, which can be further fine‐tuned by the auxiliary ligand on the gold(I) center. In the resistive memory studies, devices based on these alkynylgold(I) complexes exhibit satisfactory binary memory behaviors, demonstrating low threshold voltages in narrow distributions, high durability and low misreading rates. Such performances are believed to be originated from a field‐induced charge transfer of the alkynylgold(I) complexes, in which the electron‐accepting phosphole‐gold(I) unit plays a crucial role in stabilizing the charge transfer state and that led to the observed resistive switching and memory behavior. Abstract : A series of benzo[ b ]phosphole‐based alkynylgold(I) complexes have been synthesized and characterized. These complexes are stable in ambient conditions and display interesting photophysical behaviors tunable by the modification on donor–acceptor properties. Satisfactory resistive memory performances are observed with the representative alkynylgold(I) complexes, displaying potentials to be developed into functional multilevel resistive memories.